2020
DOI: 10.5114/aoms.2019.86798
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-1179 regulates proliferation and chemosensitivity of human ovarian cancer cells by targeting the PTEN-mediated PI3K/AKT signaling pathway

Abstract: Introduction: Owing to widespread roles of miRs, the dysregulation of their expression in human tissues has been linked with the development of several diseases such as cancer. The study was designed to investigate the role and therapeutic potential of miR-1179 in ovarian cancer. Material and methods: Proliferation rate was monitored by MTT assay. Transfections were performed using Lipofectamine 2000 reagent. Cell cycle apoptosis was detected by AO/EB and annexin V/PI staining. Expressions analysis was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The miR-1179 repression was found to inhibit proliferation and enhance the drug sensitivity of oral cancer cells to vincristine. Such implications have been drawn also previously (Zhihong et al 2019). The characterization of miR-1179 in oral cancer in this study revealed that autophagy is induced in oral cancer cells when miR-1179 transcript levels are repressed.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The miR-1179 repression was found to inhibit proliferation and enhance the drug sensitivity of oral cancer cells to vincristine. Such implications have been drawn also previously (Zhihong et al 2019). The characterization of miR-1179 in oral cancer in this study revealed that autophagy is induced in oral cancer cells when miR-1179 transcript levels are repressed.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, miR-1179 was found to be upregulated in oral cancer cells which is in accordance with several previous studies (Peng et al 2011 , Krutovskikh et al 2010 ). Further, miR-1179 downregulation was previously been shown to decline the viability of ovarian cancer cells (Zhihong et al 2019 ). Similar, observations were made from the results of the current study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because prostate cancer chemotherapy is based primarily on the use of docetaxel, therapeutic increasing FAM46C expression can be combined with existing therapies to improve therapeutic efficacy. Increasing evidences have been shown that targeting PTEN and PI3K/AKT signaling pathway can inhibit or enhance chemosensitivity of several cancer types, including prostate cancer [24,38,39]. Therefore, we suggest that FAM46C may increase the chemosensitivity of prostate cancer cells to docetaxel through the PTEN/AKT signaling pathway, even though their roles are required for further investigation.…”
Section: Agingmentioning
confidence: 85%
“…The clinical study found that the expression of PTEN protein in prostate cancer tissues was significantly lower than that in benign prostatic hyperplasia and negatively correlated to clinical Gleason score, pathological grade, and stage of prostate cancer [19,20], suggesting that PTEN protein decreases with the increase of the malignancy of prostate cancer. PI3K/AKT signaling activation can inhibit chemosensitivity and cell apoptosis and accelerate cell cycle progression, angiogenesis and cell invasion, while excessive PTEN expression can inhibit the activation of PI3K/AKT that inhibits P27 and Caspase-9 expression and promotes the translation from G1 to S phase [21][22][23][24]. Prostate cancer LNCaP cells exhibited PTEN inactivation, leading to constitutive activation of the AKT pathway [25].…”
Section: Introductionmentioning
confidence: 99%